CLORURO DE BENZALCONIO EN EL TRATAMIENTO DE LA DERMATOMICOSIS CAUSADA POR Trichophyton sp. EN EL CUY (Cavia cobayo) - Bezada Q., Sandra (2004)
The efficacy of benzalkonium chloride for the treatment of dermatomicosis caused by Trichophyton sp. in guinea pig (Cavia cobayo) was evaluated in 200 guinea pigs of two months old, that showed typical clinical signs of dermatomicosis. Hair samples and skin grudges were taken for direct exam and for in vitro culture in Dermatophytes Test Medium and Mycobiotic. Skin biopsies for pathobiology were prepared. The guinea pig were divided in groups A and B of 100 animals each. Group A was treated with 0.1% aqueous benzalkonium chloride solution, whereas group B was treated with water as placebo. All samples were positive to media culture by 3rd to 7th day and Trichophyton mentagrophytes was isolated. Sixty percent of the samples were positive to direct exam. Histological study showed mild hyperkeratosis. Healing of lesions and hair growth were observed in all treated guinea pigs by the end of 4th week. The study showed that a single application of 0.1% aqueous benzalkonium chloride solution was effective for topical treatment on guinea pig dermatomycosis.